Thermal conductivity and stability studies of cooking and waste cooking oil as a based fluid of TiO2 nanofluid for carbon steel quenching process - Rozaidi, Zaharudin; Radhiyah, Abd Aziz (Semarak Ilmu Sdn. Bhd., 2021)
Selection of quench media is important as it depends on the hardenability of the metal alloys, component’s thickness and geometry. Recently, oil and water are frequently used as a quench media in heat treatment industries. Improper quench media will cause the material to become brittle, suffers from geometric distortion, or having a high undesirable residual stress in the components. Oil was used as the fluid base in this research as the main observation focus. To obtain nanofluids and explore thermal conductivity and stability of nanofluids, the two-step method was introduced to prepare the nanofluids with 4 types of different cooking and waste cooking oil as a base fluid (Palm oil, sunflower oil, canola oil and corn oil). TiO2 powder will be mixed with oil fluid by using magnetic stirrer for 1 hour and ultrasonic bathing. Observation method used in 30 days with thermal conductivity and zeta potential to evaluate stability of each nanofluid specimens. Heat treatment onto carbon steel applied and the sample were heated at 950°C for 90 minutes and then quenched in difference oils. Microstructure and hardness analysis applied to get the result. It can conclude, adding nanoparticles in oil base fluid will enhance thermal conductivity and improve thermal performance of heat transfer of the base fluid. Quenching process with oil-based nanofluid will produce martensite structure and waste sunflower and corn oil with TiO2 it's not stable after 30 days observation but the palm and canola oil with TiO2 can achieve the highest hardness test and thermal conductivity.